Alternative scriptwriting contemporary storytelling for the screen - Dancyger, Ken; Keyt, Jessie; Rush, Jeff (Routledge, 2023)
The three-act structure is so last century! Unlike other screenwriting books, this unique storytelling guide pushes you to break free of tired, formulaic writing by bending or breaking the rules of storytelling as we know them. This new edition dives into all the key aspects of scriptwriting, including structure, genre, character, form, and tone. Authors Ken Dancyger, Jessie Keyt, and Jeff Rush explore myriad alternatives to the traditional three-act story structure, going beyond teaching you "how to tell a story" by teaching you how to write against conventional formulas to produce original, exciting material. Fully revised and updated, the book includes new examples from contemporary and classic cinema and episodic series, as well as additional content on strategies for plot, character, and genre; an exploration of theatrical devices in film; and approaches to scriptwriting with case studies of prolific storytellers such as Billy Wilder, Kelly Reichardt, Phoebe Waller-Bridge, and Kathryn Bigelow. Ideal for students of screenwriting and professional screenwriters wishing to develop their craft and write original scripts"--Provided by publisher.